Estimation of dietary fiber in university students - Tapia Diaz, Angela (2022)
Objective: Determine the estimation of dietary fiber of nursing students from a private university, Chiclayo 2020. Method: This study was quantitative, the design was non-experimental, descriptive, cross-sectional. The population consisted of 294 students from the nursing school, the sample was stratified of 164 students, selected by simple random sampling. As a technique, the survey was used and the instrument was the “Food consumption frequency questionnaire” and a “24-hour reminder (R24H)”. The research took into account the criteria of scientific rigor and ethical principles of Belmont, and for data processing the SPSS v 25 program was used. Main results: It obtaining as a result that the average consumption of dietary fiber of the nursing students was 15, 37 gr. / day; Regarding the frequency of food consumption according to the food source, a consumption within the recommended was found in the groups of cereals (55.5%), legumes (48.8%), meats (58.5%), Added fats and sugars (55.5%), but low in fruits (36.6%), vegetables (37.8), dairy (33.5%) and water (44.5%). Overall conclusion: That the estimate of dietary fiber intake gr /day is less than that recommended by the WHO-FAO.